2022
DOI: 10.3389/fimmu.2022.1021695
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Atractylodes macrocephala Koidz. ameliorates DSS-induced colitis in mice by regulating the Th17/Treg cell balance

Abstract: Atractylodes macrocephala Koidz. is one of the most frequently used traditional Chinese medicines for the treatment of ulcerative colitis (UC). The beneficial effect of polysaccharide from Atractylodes macrocephala Koidz. (PAMK) on UC has been reported, while the underlying mechanism and target remain unclear. In this study, we systematically investigated the therapeutic effect and the underlying mechanism of PAMK in UC based on a mouse model of dextran sodium sulfate (DSS)-induced colitis. PAMK treatment (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Sensitivity Analysis. After excluding the study conducted by Yang [19], we observed heterogeneity in the spleen index during this meta-analysis. Upon thorough review and comparison with other studies analyzing the spleen index, we found a notable distinction between Yang's study and the others, primarily regarding the age of the mice used.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Sensitivity Analysis. After excluding the study conducted by Yang [19], we observed heterogeneity in the spleen index during this meta-analysis. Upon thorough review and comparison with other studies analyzing the spleen index, we found a notable distinction between Yang's study and the others, primarily regarding the age of the mice used.…”
Section: Discussionmentioning
confidence: 89%
“…( 2) Anti-inflammation: Excessive production and abnormal activation of inflammatory factors can result in an inflammatory response in the intestinal mucosa, leading to impaired barrier function and an imbalance in fluid secretion and absorption, ultimately causing diarrhea [28]. AMK has the potential to alleviate intestinal mucosal inflammation by inhibiting the activation of Drp1 and NLRP3 inflammasomes [17], suppressing NF-κB and STAT3 signaling [19,25], modulating the MAPK/NF-κB pathway [22], activating PPARα [23], reducing the secretion of pro-inflammatory factors such as IL-1β, IL-6, IL-17, and TNF-α, and enhancing the secretion of IL-10. (3) Anti-oxidation: Antioxidation is a factor that helps prevent the worsening of diarrhea [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atractylodes macrocephala Koidz (AM) is an important traditional Chinese medicine. The polysaccharide from AM (AMP), as one of the main active components, has antiinflammatory [9], antioxidant [10] and immunomodulatory activities [11]. Concurrently, zinc oxide nanoparticles (ZnONPs) exhibit immunomodulatory properties, capable of activating dendritic cells, leading to the production of cytokines such as IL-6 and TNF-α [12].…”
Section: Introductionmentioning
confidence: 99%